A novel, dual cytokine‐secretion assay for the purification of human Th22 cells that do not co‐produce IL‐17A. Issue 1 (4th November 2015) - Wawrzyniak, M.; Ochsner, U.; Wirz, O.; Wawrzyniak, P.; van de Veen, W.; Akdis, C. A.; Akdis, M.
Abstract: Background: Interleukin‐22 is produced by certain T helper cells subsets (Th17, Th22) and at lower levels by γ‐δ T cells, NKT and innate lymphoid cells. Th22 cells are unique immune cells that regulate tissue responses by IL‐22 production. The exact discrimination between Th17 cells that co‐produce IL‐22 and single IL‐22‐producing Th22 cells has not been possible until the present study. Isolation of pure Th22 cells without co‐expression of cytokines of other T‐cell subsets is essential to better understand their function in humans. The aim of this study is the isolation and characterization of viable, human IL‐22‐producing CD4+ T cells that do not produce IL‐17A. Methods: Isolation of viable Th22 cells was performed with the combination of two cytokine secretion assays detecting IL‐17A‐ and IL‐22‐producing cells in a single purification step. Results: The newly developed cytokine secretion assay consists of anti‐IL‐22 and anti‐IL‐17A catch antibodies, which via biotin–streptavidin interaction are bound to the biotinylated surface of the target cell, and anti‐IL‐22 and IL‐17A detection antibody labelled with a fluorescent dye, which detects cytokines bound to these catch antibodies. A unique population of human Th22 cells, which do not produce IL‐17A, was sorted, and cytokine expression pattern was confirmed by quantitative PCR analysis and ELISA. The presented technique allows the detection and isolation of pure human Th22 cells. Conclusions: This technique may allow the purification of any single cytokine‐producing cell subset, and the combination of several different cytokine secretion assays can be used to purify and characterize novel and unique cell subsets.